1996
DOI: 10.1074/jbc.271.41.25515
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a Novel Mouse Macrophage Gene That Encodes a Nuclear Protein Comprising Polyglutamine Repeats and Interspersing Histidines

Abstract: Simple tandem repeats of the trinucleotide sequence CAG encode homopolymeric stretches of glutamine. Although polyglutamine has been identified in diverse proteins, it is present predominantly in transcription factors. We observed that oncogene-immortalized mouse macrophages express several genes that contain a CAG repeat motif. Therefore, we attempted to clone a novel gene that contains a CAG repeat and is associated with cytokine activation of macrophages. Screening of a mouse macrophage cDNA library with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…Although Nocte has no apparent DNA binding domain, the presence of poly-Q and poly-A stretches also suggests that Nocte may function as transcription cofactor (Riley and Orr, 2006), which is further supported by a stretch of 268 amino acids showing weak homology to the mammalian Glutamine Rich Protein 1 (GRP-1) ( Figure 3C; Cox et al, 1996). Comparison with available genome sequences revealed that nocte is distributed among insects (i.e., not only Drosophilidae; Figure 3C), but no obvious vertebrate homolog was identified (Experimental Procedures).…”
Section: Neuronmentioning
confidence: 90%
“…Although Nocte has no apparent DNA binding domain, the presence of poly-Q and poly-A stretches also suggests that Nocte may function as transcription cofactor (Riley and Orr, 2006), which is further supported by a stretch of 268 amino acids showing weak homology to the mammalian Glutamine Rich Protein 1 (GRP-1) ( Figure 3C; Cox et al, 1996). Comparison with available genome sequences revealed that nocte is distributed among insects (i.e., not only Drosophilidae; Figure 3C), but no obvious vertebrate homolog was identified (Experimental Procedures).…”
Section: Neuronmentioning
confidence: 90%
“…Homopolymeric tracts of glutamine are not uncommon and have been found in a number of mammalian transcription factors (5,6,11,12,25). Moreover, recent studies have shown that homopolymeric stretches of glutamines are also found in other serine/threonine protein kinases which have a high degree of similarity with C. trifolii TB3.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the mouse homolog of MBT-1 harbors a unique glutamine-rich domain (poly-Q), which is absent in human MBT-1. This domain probably strengthens protein-protein interactions, resulting in the polymerization/ aggregation of nuclear molecules, as in macrophage glutamine repeat protein-1 (GRP-1) (Cox et al, 1996). Other components are, however, highly conserved in human and mouse clones ( Figure 1A).…”
Section: Mbt-1 a New Pcg Gene Expressed In Hematopoietic Progenitor mentioning
confidence: 99%